2013
DOI: 10.1080/09712119.2013.792734
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of Zackel sheep through cross-breeding with prolific Bluefaced Leicester under semi-intensive and extensive production systems

Abstract: The aim of the current research was to evaluate the effects of cross-breeding Romanian indigenous Turcana (TA) ewes belonging to the Zackel breed group with prolific Bluefaced Leicester (BL) rams on the performance and reproduction rates of F 1 cross-bred descendants under semi-intensive and extensive production systems. The UK stratified sheep production system was applied for the development of the cross-breeding scheme. F 1 Bluefaced Leicester )Turcana (F 1 BL )TA) cross-bred ewes proved to be highly precoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Lamb meat consumption in children with atopic dermatitis and multiple food hypersensitivity has resulted in signifi cant clinical improvements. Lamb meat has a special importance in infant nutrition, because it provides a unique [19][20][21][22]. These analyzes have shown that many factors in the production, such are diet, age of weaning, breed, sex and body weight, have effects on muscle fatty acid composition and sensory characteristics of lamb meat [15,23].…”
Section: Discussionmentioning
confidence: 99%
“…Lamb meat consumption in children with atopic dermatitis and multiple food hypersensitivity has resulted in signifi cant clinical improvements. Lamb meat has a special importance in infant nutrition, because it provides a unique [19][20][21][22]. These analyzes have shown that many factors in the production, such are diet, age of weaning, breed, sex and body weight, have effects on muscle fatty acid composition and sensory characteristics of lamb meat [15,23].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, the usefulness of Zackel sheep was repeatedly improved through cross-breeding with other more noble breeds [31,32]. In the late 19th and the early 20th centuries, several attempts of improving Polish Zackel were undertaken.…”
Section: Mountain Sheep and Their Products 31 Sheep Breedsmentioning
confidence: 99%
“…High reproductive performance, carcass quality, and low input cost are important to ensure profitable production in sheep breeding (Macit et al, 2001). The efficiency of lamb production is affected by reproduction, mothering ability and milk production of the ewes, and growth rate and survival rate of the lambs (Rao & Notter, 2000;Mishra et al, 2007;Gavojdian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%